Transition from Low Potassium Olivine Tholeiites to Alkali Basalts on Ubekendt Ejland. : The Tertiary Volcanic Province of West Greenland. - Gutzon Larsen, Jørgen (Meddelelser om Grønland, 1977)
Five basalt types are distinguished in a 4-5 km thick volcanic pile of the upper formations on Ubekendt Ejland, the Tertiary province of West Greenland. They were erupted in the following order: 1) low potassium olivine tholeiites, 2) transitional basalts with tholeiitic affinity, 3) transitional basalts with alkaline affinity, 4) plagioclase rich alkali basalts, 5) olivine-clinopyroxene porphyritic alkali basalts. A multiparental origin is suggested for type 1-4 and even for rocks belonging to the same type. Possibly slightly different MgO rich magmas represented by the picritic lavas of the province could have formed the basalts of type 1-3 by fractional crystallization at low pressure up to a pressure of about 8 kb. The type 5 basalts were either formed by high pressure fractional crystallization combined with zone refining, or by a small degree of partial melting.